THE EVALUATION OF STRENGTH AND DYNAMIC CHARACTERISTICS OF THE SPRING INCREASE OF PASSENGER TRUCKS - S. V. Myamlin; V. V. Zhyzhko; V. I. Prykhodko; O. A. Shkabrov (Nauka ta progres transportu, 2009)
In the paper the results of calculations on determination of strength features of springs in the spring suspension of passenger coach bogies and their dynamic characteristics with the account of requirements of normative documentation are presented.